2011
DOI: 10.1007/s00284-011-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Genus Acinetobacter with the Decomposition of a Swine Carcass and the Isolation and Characterization of a Novel Strain of Acinetobacter sp. P4

Abstract: Using fluorescence in situ hybridization (FISH) and a selective and differential medium, Acinetobacter numbers were enumerated over the time course of decomposition, from fresh to putrid/dry, of a swine carcass. In addition, Acinetobacter diversity and succession were also characterized. Acinetobacter bacterial counts were observed to be the lowest before exposure (undetectable) and increased to their highest during active decay then decreased and leveled during advanced decay through putrid/dry. FISH analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Acinetobacter immediately increased in abundance at hour 8 in brain samples (Fig. S1), which is an aerobic, non fermentative, gram-negative pathogenic bacilli and previously reported in a swine carcass using fluorescence in situ hybridization (FISH) [26]. Cupriavidus and Agrobacterium were increased after 8 h of decomposition in brain samples.…”
Section: Discussionsupporting
confidence: 74%
“…Acinetobacter immediately increased in abundance at hour 8 in brain samples (Fig. S1), which is an aerobic, non fermentative, gram-negative pathogenic bacilli and previously reported in a swine carcass using fluorescence in situ hybridization (FISH) [26]. Cupriavidus and Agrobacterium were increased after 8 h of decomposition in brain samples.…”
Section: Discussionsupporting
confidence: 74%
“…Incremental models were fit to assess the influence of groups of covariates: 1) demographics, 2) then adding socioeconomic status (defined by highest education obtained and household income), and 3) adding stroke risk factors. As there was some racial difference in terms of medical records obtained, we applied a mathematical correction for the final model to ensure that this bias did not alter our results 15 . We included the following covariates in all final models: age, race, sex, region of residence, education, income, alcohol intake, current smoking, and a history of diabetes, hypertension, myocardial infarction, atrial fibrillation, and dyslipidemia.…”
Section: Methodsmentioning
confidence: 99%
“…These microbes contribute significantly to decomposition (e.g., putrefaction) and can release volatile organic compounds that attract insects and scavengers . Recent postmortem microbiology has demonstrated that bacterial phyla Actinobacteria, Bacteroidetes, Firmicutes, and Proteobacteria are regularly associated with decomposing remains regardless of carcass species, season, or soil type . However, despite the surge of interest in postmortem microbiology, few studies have investigated the microbial communities associated with insect larval masses.…”
mentioning
confidence: 99%